Settlement Patterns and Subarctic Development the South Mackenzie, N. W. T. - Pearson, Roger (Anthropologica, 2022)
Throughout most of the Northwest Territories forces of economic decline and population increase and concentration have produced serious socio-economic problems, which are possibly best alleviated by out-migration. In contrast, the South Mackenzie area possesses adequate and expanding economic resources to meet the population changes. Current settlement patterns and policies, however, inhibit goal achievement.